2022
DOI: 10.51253/pafmj.v72i2.4168
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diagnostic Accuracy of Real Time Shear Wave Elastography in Detecting Liver Cirrhosis Keeping Histopathology as Reference Standard

Abstract: Objective: To determine the diagnostic accuracy of real-time Shear Wave Elastography (SWE) in detecting liver cirrhosis among patients suffering from diseases predisposing to it, keeping histopathology as the reference standard. Study Design: Cross-sectional study. Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi, from Jan 2018 to Jul 2018. Methodology: A total of 114 patients were recruited, and relevant history taken from patientsreal-time shear wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Several studies have therefore used ML models to diagnose patients with different HCV stages. A recent study by [13] assessed the accuracy of real-time shear wave elastography in identifying liver cirrhosis. The study concluded that this technique reached 92.86% sensitivity, 89.66% specificity, and 91.23% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have therefore used ML models to diagnose patients with different HCV stages. A recent study by [13] assessed the accuracy of real-time shear wave elastography in identifying liver cirrhosis. The study concluded that this technique reached 92.86% sensitivity, 89.66% specificity, and 91.23% accuracy.…”
Section: Introductionmentioning
confidence: 99%